2023
DOI: 10.1007/s10668-023-03101-7
|View full text |Cite
|
Sign up to set email alerts
|

Green practices implementation for environmental sustainability by five-star hotels in Kampala, Uganda

Abstract: Hotels operate continuously and are known to be one of the contributors of global pollution. Strategies like adoption of green practices would be a remedy to mitigate pollution and their effects for environmental sustainability. This study focused on green practice's implementation by the five-star hotels in Kampala district, Uganda. Specifically, it explored the benefits achieved and effects encountered by the management of the hotels as a result of implementing green practices. A questionnaire survey and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…These findings are supported by past research by Barakagira and Paapa (2023) who found that hotels with a strong environmental concern were more likely to engage in resource conservation, waste management, and energy efficiency initiatives. Similarly, a more recent study by Xess et al (2021) observed a positive relationship between environmental concern and the adoption of eco-friendly technologies in hotels.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These findings are supported by past research by Barakagira and Paapa (2023) who found that hotels with a strong environmental concern were more likely to engage in resource conservation, waste management, and energy efficiency initiatives. Similarly, a more recent study by Xess et al (2021) observed a positive relationship between environmental concern and the adoption of eco-friendly technologies in hotels.…”
Section: Discussionsupporting
confidence: 79%
“…As a result, GHRM is critical to environmental management because HRM plays a critical part in achieving the organization's environmental goals (Pham et al, 2019). In particular, hotels ought to be interested in going green because it can enhance brand recognition and reputation, draw eco-conscious clients, lower expenses, secure environmental certifications, and adhere to legal environmental requirements (Barakagira & Paapa, 2023). At presently, stakeholders are paying close attention to environmental sustainability and as a result, businesses use a variety of tactics to fulfil their corporate social responsibility (CSR) obligations (Barakagira & Paapa, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy-efficiency and increased use of less carbon-concentrated fuels are the two widely cited group of energy conservation practices. These include the use of renewable energy sources such as solar and wind power, the implementation of energy control systems, and the installation of energy-efficient equipment and gadgets (Barakagira & Paapa, 2023;Cingoski & Petrevska, 2018;Fadhili, 2015;Kularatne et al, 2019).…”
Section: Energy Conservation Practices and Performance Of Accommodati...mentioning
confidence: 99%
“…While various studies (e.g., Barakagira and Paapa, 2023;Chomba, Bichage and Kariuki, 2022;Cingoski and Petrevska, 2018;Kularatne et al, 2019;Langgat et al, 2023;Moise et al, 2021) have been dedicated to assessing level of implementation of environmentally friendly practices and their effect on performance, few such studies have focused on energy conservation practices and performance of lodges and camps in Kenya. The findings of the few studies are also contradictory.…”
Section: Energy Conservation Practices and Performance Of Accommodati...mentioning
confidence: 99%